4-Hydroxynonenal Contributes to Fibroblast Senescence in Skin Photoaging Evoked by UV-A Radiation - Audrey Swiader; Caroline Camaré; Paul Guerby; Robert Salvayre; Anne Negre-Salvayre (MDPI AG, 2021)
Solar ultraviolet A (UV-A) radiation promotes a huge variety of damages on connective tissues and dermal fibroblasts, including cellular senescence, a major contributor of skin photoaging. The mechanisms of skin photoaging evoked by UV-A partly involve the generation of reactive oxygen species and lipid peroxidation. We previously reported that 4-hydroxynonenal (HNE), a lipid peroxidation-derived aldehyde, forms adducts on elastin in the skins of UV-A irradiated hairless mice, possibly contributing to actinic elastosis. In the present study, we investigated whether and how HNE promotes fibroblast senescence in skin photoaging. Dermal fibroblasts of skins from UV-A-exposed hairless mice exhibited an increased number of γH2AX foci characteristic of cell senescence, together with an accumulation of HNE adducts partly colocalizing with the cytoskeletal protein vimentin. Murine fibroblasts exposed to UV-A radiation (two cycles of 15 J/cm2), or HNE (30 µM, 4 h), exhibited senescence patterns characterized by an increased γH2AX foci expression, an accumulation of acetylated proteins, and a decreased expression of the sirtuin SIRT1. HNE adducts were detected on vimentin in cultured fibroblasts irradiated by UV-A or incubated with HNE. The HNE scavenger carnosine prevented both vimentin modification and fibroblast senescence evoked by HNE in vitro and in the skins of UV-A-exposed mice. Altogether, these data emphasize the role of HNE and lipid peroxidation-derived aldehydes in fibroblast senescence, and confirm the protective effect of carnosine in skin photoaging.